Lagoon water-level oscillations driven by rainfall and wave climate - Gonzalez-Villanueva, R. (2019)
Barrier breaching and subsequent inlet formation represent critical processes that ensure the temporary or permanent connection and transference of water, nutrients, or living organisms between a lagoon and the open sea. Here, we investigate the conditions inducing natural barrier breaching through a 34 months monitoring program of water-level oscillations within a shallow lagoon and the adjacent nearshore, at the Northern coast of the Iberian Peninsula, Louro lagoon. Seven natural openings were identified to have occurred during the three monitored wet seasons, from the 2009 to 2012, (Wet1, Wet2 and Wet3); four in the Wetl, two in the Wet2 and one in. the Wet3. The openings were grouped in three types depending on the observed relation between the lagoon water-level (L-wl), the estimated berm height (B-h) and the water-level at the beach (B-wl): (i) openings by lagoon outflow, which include those characterized by L-wl higher than B-h and lower B-wl; (ii) openings by wave inundation, including those induced by B-wl higher than B-h, and (iii) mixed openings, which result from a combination of the two previous conditions. We observed that L-wl is modulated by the rainfall regime (R-f) and can be explained by the accumulated precipitation. We estimated applying runup equations to obtain B-h and B-wl which depend on the wave climate and tidal level. The inlet lifespan was found to be regulated by the wave climate and rainfall regime; in particular barrier sealing was associated with a sudden increase in wave period and a reduction in precipitation. This work proves that the natural openings could be predicted successfully with support to medium term water-level monitoring programs, which in turn may significantly contribute to strategic decision making for management and conservation purposes.